2019
DOI: 10.1111/srt.12762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating nail thickness and stiffness with shear‐wave elastography in nail psoriasis: A preliminary study

Abstract: Psoriasis is a chronic inflammatory disease affecting up to 3% of the general population. The disease is multifactorial; genetic and environmental factors play a role in the pathogenesis. 1 Nail involvement is observed in 10% of psoriatic patients, but the risk of occurrence of such changes during a patient's lifetime may be as high as 80%-90%. 2 Nail psoriasis has a significant negative impact on quality of life, and it may also be considered an indicator for patients at risk for future psoriatic joint damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first study that uses SWE in patients with PsO, except for a previous study that used SWE in subjects with nail PsO. 39 In our study, we observed that psoriatic plaque had a marked degree of hardness compared to the skin not affected by dermatopathy before topical treatment with calcipotriol+betamethasone foam. On the contrary, after pharmacological treatment, in a parallel way to a significant reduction of the PASI, there was a statistical significative decrease of plaque skin hardness that highlights a correlation between these parameters, in particular between plaque activity and its hardness.…”
Section: Discussionmentioning
confidence: 44%
“…To the best of our knowledge, this is the first study that uses SWE in patients with PsO, except for a previous study that used SWE in subjects with nail PsO. 39 In our study, we observed that psoriatic plaque had a marked degree of hardness compared to the skin not affected by dermatopathy before topical treatment with calcipotriol+betamethasone foam. On the contrary, after pharmacological treatment, in a parallel way to a significant reduction of the PASI, there was a statistical significative decrease of plaque skin hardness that highlights a correlation between these parameters, in particular between plaque activity and its hardness.…”
Section: Discussionmentioning
confidence: 44%
“…A total of 753 articles were screened and 67 articles included, as depicted in the PRISMA flow diagram in Figure 1 9‐75 . The number of articles per technique varied substantially, ranging from 36 for US to just one on PET/CT.…”
Section: Resultsmentioning
confidence: 99%
“…In dermatology, this parameter is used to evaluate the therapeutic efficacy of various treatments in conditions such as psoriasis, 9,55,66 localized scleroderma, 67 systemic sclerosis, 4,42 hidradenitis suppurativa 10 and atopic dermatitis 64 . In addition, measurements of the skin lesion area, diameter and dimensions are also used in the diagnosis, characterization and evaluation of skin disease treatments 61,65,68–72 …”
Section: Main Metric Parameters Of Analysis By Hfusmentioning
confidence: 99%